1968
DOI: 10.1901/jeab.1968.11-819
|View full text |Cite
|
Sign up to set email alerts
|

SCHEDULES USING NOXIOUS STIMULI. III. RESPONDING MAINTAINED WITH RESPONSE‐PRODUCED ELECTRIC SHOCKS1

Abstract: Responding was maintained in two squirrel monkeys under several variations of a 10-min fixed-interval schedule of electric shock presentation. The monkeys were first trained under a 2-min variable-interval schedule of food presentation, and then under a concurrent schedule of food presentation and shock presentation. In one monkey, when shocks (12.6 ma) followed each response during the last minute of an 11-min cycle ending with a timeout period, responding was increased during the first 10 min and suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
0
1

Year Published

1969
1969
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(100 citation statements)
references
References 24 publications
(24 reference statements)
9
90
0
1
Order By: Relevance
“…The current study provides an additional exception. These observations are consistent with the conclusions of Kelleher and Morse (1968) and Rachlin (1966) that a subject's history with shock is one determinant of how shock will affect behavior. Similar effects of experimental history have also been reported when positive reinforcement was used (e.g., Franks & Lattal, 1976).…”
Section: Discussionsupporting
confidence: 89%
“…The current study provides an additional exception. These observations are consistent with the conclusions of Kelleher and Morse (1968) and Rachlin (1966) that a subject's history with shock is one determinant of how shock will affect behavior. Similar effects of experimental history have also been reported when positive reinforcement was used (e.g., Franks & Lattal, 1976).…”
Section: Discussionsupporting
confidence: 89%
“…The empirical half of the law has survived relatively intact. Punishment is effective in reducing the future probability of a response (Azrin and Holz, 1966;Fantino, 1973;Mackintosh, 1974;-but see Kelleher and Morse, 1968). Thorndike's theoretical interpretation has not fared as well.…”
mentioning
confidence: 99%
“…This indieates that, although the rate of presentation of response-contingent shock may determine whether an inerease or a deerease in responding oceurs (Kelleher & Morse, 1968), the schedule of shock presentation, itself, is an important faetor.…”
Section: Resultsmentioning
confidence: 93%
“…It is therefore possible that this effect is limited to this type of species, especially as the effect is not limited to situations using an avoidance baseline. Kelleher & Morse (1968) have shown that an FI schedule of response-contingent shock increases responding on a VI schedule of food presentation, an'd Morse, Mead, & Kelleher (1967) showed that noncontingent shocks, which originally elieited responses, could later be used to reinforce responding when there was no other schedule of reinforcement in operation and shocks were made response-contingent. Both of these experiments used squirrel monkeys as Ss.…”
Section: Resultsmentioning
confidence: 99%